2014
DOI: 10.1007/s00167-014-2888-6
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a virtual-reality-based simulator using passive haptic feedback for knee arthroscopy

Abstract: PURPOSE The aim of this work is to determine face validity and construct validity of a new virtual-reality-based simulator for diagnostic and therapeutic knee arthroscopy. METHODS The study tests a novel arthroscopic simulator based on passive haptics. Sixty-eight participants were grouped into novices, intermediates, and experts. All participants completed two exercises. In order to establish face validity, all participants filled out a questionnaire concerning different aspects of simulator realism, training… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
51
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(64 citation statements)
references
References 36 publications
10
51
0
3
Order By: Relevance
“…Furthermore, all of the participating experienced surgeons thought that procedure 5 did not resemble a realistic meniscus resection by any means, thus also lacking content validity 15 , and for these reasons, the procedure was excluded from the test. Other literature has also found that the current commercially available virtual reality arthroscopy simulators are somewhat deficient with regard to therapeutic procedures 3,4, 16 .…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Furthermore, all of the participating experienced surgeons thought that procedure 5 did not resemble a realistic meniscus resection by any means, thus also lacking content validity 15 , and for these reasons, the procedure was excluded from the test. Other literature has also found that the current commercially available virtual reality arthroscopy simulators are somewhat deficient with regard to therapeutic procedures 3,4, 16 .…”
Section: Discussionmentioning
confidence: 96%
“…It is also important to notice that the simulator only allows us to assess certain technical skills important to diagnostic knee arthroscopy. Other essential technical skills such as the optimal placement of portals 16 and nontechnical skills such as the ability to set correct indications for surgery are not assessed. Furthermore, locating and palpating blue spheres at defined landmarks is a rather simplified surrogate target for a diagnostic arthroscopy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple studies have demonstrated the construct validity of simulators by showing a correlation between a surgeon's experience and their performance on a simulator. [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] The procedures where this has been reported include diagnostic and therapeutic knee, hip and shoulder arthroscopy, hip fracture fixation, the fixation of complex intra-articular fractures and basic orthopaedic skills, including drilling (Table II). Studies assessing learning curves.…”
Section: Resultsmentioning
confidence: 99%
“…Realism-wise, the quantifying mostly comes with a question about the realistic-ness of the experimentation a subject just gone through (which is to be tied to the fourth acceptation, ''psychological realism"). A more detailed approach goes through questionnaires (Fucentese et al, 2015;Gaelle et al, 2014). There are though different other approaches that are to be highlighted:…”
Section: Scope Of Workmentioning
confidence: 99%